An experimental analysis of unintentional lower limb action. - Riddoch, M; Humphreys, G; Edwards, MG (2001)
We provide an experimental analysis of the factors that determine unintentional lower limb action in a patient with cortico-basal degeneration. We show a dissociation between lower limb movements in a novel task and the ability to remember task instructions. In addition, there were effects of the pre-potency of the learned response to the stimulus, with different effects emerging with familiar and unfamiliar stimuli.